Analisis Perbandingan Kinerja Perusahaan Pengakuisisi Sebelum dan Sesudah Akuisisi Pada Tahun 2016 - Dewi, Angdriani Puspita; Hartono, Ulil (Jurnal Ilmu Manajemen, 2020)
The expansion was one or other business strategies which every company typically do to compete in the global market. The successful acquisition was assessed based on the acquiring company’s financial performance ratio between before and after the acquisition. The function of this paper to analyze the financial performance of acquiring company’s who perform an acquisition in 2016 period which is proxied with the ratio finance Current Ratio (CR), Debt to Equity (DER), Debt to Asset (DAR), Return on Equity (ROE), and Return on Asset (ROA). The analytical technique used was the Paired Sample T-test for normally distributed data and the Wilcoxon Sign Rank Test for abnormally distributed data. Based on the outcome of the analysis develop that company’s financial performance as intended by financial ratios are Current Ratio (CR), Debt to Equity (DER), Debt to Asset (DAR), Return on Equity (ROE), and Return on Assets (ROA) not significantly different after the acquiring considered to before the acquiring. This research proves that the acquisition strategy does not always guarantee an increase in a company’s financial performance after acquiring.